1967
DOI: 10.1099/00221287-48-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Changes in Bacteroids of Rhizobium lupini During Nodule Development

Abstract: SUMMARYThe nodules of yellow lupin plants (Lupinus Zuteus L.) increased logarithmically in wet weight, leghaemoglobin and rhizobial numbers. Bacteroids were isolated from such nodules and the changes in concentration of protein, RNA and DNA per organism were followed as a function of nodule age. Six weeks after emergence, DNA and RNA per organism had fallen to 40 yo and 13%, respectively, of the values found in the bacteria from 1-week-old nodules. No further changes in RNA and DNA were found after this time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Bergersen (2) observed no difference in deoxyribonucleic acid (DNA) content per microorganism between cultured Rhizobiumjaponicum and soybean bacteroids. Dilworth and Williams (7) reported a twoto threefold decrease in DNA content per bacteroid in Lupinus species during the first few weeks of nodulation. Sutton (12), working with rhizobia associated with Lotus species, found no difference in DNA content among bacteroids and cultured rhizobia for a slow-growing Rhizobium strain and a lower DNA content per bacteroid for a fast-growing strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bergersen (2) observed no difference in deoxyribonucleic acid (DNA) content per microorganism between cultured Rhizobiumjaponicum and soybean bacteroids. Dilworth and Williams (7) reported a twoto threefold decrease in DNA content per bacteroid in Lupinus species during the first few weeks of nodulation. Sutton (12), working with rhizobia associated with Lotus species, found no difference in DNA content among bacteroids and cultured rhizobia for a slow-growing Rhizobium strain and a lower DNA content per bacteroid for a fast-growing strain.…”
mentioning
confidence: 99%
“…These results indicate that the incapability of bacteroids to reestablish growth in nutrient media may not be caused by a decrease in nucleic acid content of the symbiotic rhizobia.It has been shown that the growth of symbiotic rhizobia (bacteroids) cannot be reestablished in nutrient media (1, 3). One reason for the nonviability of bacteroids has been attributed to a decrease in nucleic acid content of the symbiotic rhizobia (7). However, previous attempts to determine the nucleic acid content of symbiotic rhizobia has provided conflicting results (3, 7, 10, 12).…”
mentioning
confidence: 99%
“…Attempts to determine which developmental stage each of these fractionated populations represents, are still difficult. Microscopic examination of nodules reveals the predominant location of certain bacteroids with respect to size, shape, and morphological form but it is difficult to relate these morphological parameters to changes in such physiological or biochemical parameters as enzyme activities and nucleic acid content (1,6,10,11), which also are known to accompany the developmental process. This communication reports an effort to relate the morphological, physiological, and biochemical changes in alfalfa bacteroids through the combined use of electron microscopy, gas chromatography, and laser flow microfluorometry.…”
mentioning
confidence: 99%
“…Contaminants were present in the bacteroid suspensions used (Table I) but we do not consider that they were responsible for the protein synthesis observed. Although bacteroids do not reproduce, increases in protein per bacteroid have been recorded during the development of the same strain isolated from lupin nodules (Dilworth & Williams, 1967), and the examination of a variety of contaminant bacteria under the light microscope showed them to be uniformly small organisms. Caution has to be observed with comparisons of calculated protein synthesis by the contaminants and the observed [3H]leucine incorporation into cellular protein, but the incorporation reported in Inhibitory efects of antibiotics Incubation of both bacteroids and bacteria in the presence of 0 -1 mM D-threo-chloramphenicol inhibited protein synthesis (Fig.…”
Section: Contaminating Organismsmentioning
confidence: 99%